Taylor -Fixed point homotopy for solving nonlinear algebraic problems - Hasan, Talib Hashim; Chowdhury, Md. Sazzad Hossien; Yamamura, Kiyotaka (2010)
In this paper we tried to exploit homotopy approximation methods (HAM) for solving nonlinear algebraic equation NLAE. HAM can be considered as one of the new methods belong to the general classification of the computational methods which can be used to find the numerical solution of many types of the problems in science and engineering. In this work, we solved NLAE using fixed-point homotopy based on Taylor series. Numerical example is given to show the effectiveness of the purposed method using MATLAB language.